Exploring Vacuum Compression Molding as a Preparation Method for Flexible-Dose Pediatric Orodispersible Films - Dana Hales; Cătălina Bogdan; Lucia Ruxandra Tefas; Andreea Cornilă; Maria-Andreea Chiver; Ioan Tomuță; Tibor Casian; Rareș Iovanov; Gábor Katona; Rita Ambrus; Sonia Iurian (MDPI AG, 2024)
In recent years, solid dosage forms have gained interest in pediatric therapy because they can provide valuable benefits in terms of dose accuracy and stability. Particularly for orodispersible films (ODFs), the literature evidences increased acceptability and dose flexibility. Among the various available technologies for obtaining ODFs, such as solvent casting, hot-melt extrusion, and ink printing technologies, the solvent-free preparation methods exhibit significant advantages. This study investigated Vacuum Compression Molding (VCM) as a solvent-free manufacturing method for the preparation of flexible-dose pediatric orodispersible films. The experimental approach focused on selecting the appropriate plasticizer and ratios of the active pharmaceutical ingredient, diclofenac sodium, followed by the study of their impacts on the mechanical properties, disintegration time, and drug release profile of the ODFs. Additional investigations were performed to obtain insights regarding the solid-state properties. The ODFs obtained by VCM displayed adequate quality in terms of their critical characteristics. Therefore, this proof-of-concept study shows how VCM could be utilized as a standalone method for the production of small-scale ODFs, enabling the customization of doses to meet the individual needs of pediatric patients.